Productivity and economics of late sown rapeseed (Brassica campestris var. Toria) after winter rice under varying irrigation and nutrient levels (Journal of Oilseed Brassica, 2026)
A field experiment was conducted during Rabi season, 2014-15 to 2016-17 at Assam Agricultural University, Jorhat, Assam to study the effect of irrigation and fertilizer on late sown rapeseed (Brassica campestris var. Toria) grown after rice with 4 irrigation regimes viz., rainfed, 6 cm irrigation at pre- flowering stage (25 DAS), 6 cm irrigation at siliqua formation stage (50 DAS) and 6 cm irrigation at pre- flowering (25 DAS) and siliqua formation stage (50 DAS) with three different fertilizer levels viz., 45-30-30, 60-40-40 and 75-50-50 N-P2O5-K2O kg ha-1. Two irrigations applied at pre-floweringand siliqua formation stage recorded the highest chlorophyll stability index, growth viz., plant height, number of branches plant-1 and leaf area index and yield attributes viz., siliquae plant-1 and number of seeds siliqua-1. Two irrigations at preflowering- and siliqua formation stage also recorded higher seed- and stover yield than one irrigation at flowering, one irrigation at siliqua formation and rainfed crop. This treatment also recorded the highest mean net return (Rs. 15562/ha) and B:C ratio (1.76). However, among the fertilizer levels, application of 75-50-50 N-P2O5-K2O kg ha-1 being at par with 60- 40-40 N-P2O5-K2O kg ha-1 recorded the highest growth, yield attributes and seed- and stover yield. The highest water use efficiency (WUE) was observed under rainfed condition.